CULTURAL SYMBOLISM IN ROB MARSHALL’S MEMOIR OF A GEISHA MOVIE - Chairi Ichwana Syahputri and Zainuddin (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study deal with symbolic element and its meaning in Rob Marshall’s Memoir of a Geisha movie. The objectives of this study were to find out the kinds of symbol in the movie and to describe the meaning of the symbol. This study was conducted by using descriptive qualitative method. The data of this study was analyzed by using five steps: identifying the symbolic element in Memoir of a Geisha movie, reducing the symbols, classifying the symbols to its kinds, analyzing the meaning of the symbols and concluding the symbolic element that are founded. The data were collected from the movie Memoir of a Geisha. The finding of this study found that there were 21 symbols in the movie. Those symbols were red, black, white, throwing salt, burn incense, kibiri, serving tea, snow dance, mizuage, tunnel, cherry blossom, maple leaves, water, fire, full-coloured lip, kimono, bell flower crest, obi, rice cake in red box, golden fish and tiger. The meaning of the symbols were dangerous, joy, evil, formality, status, purify, good luck, honor, forbidden love, the practice, demarcation point, spring, autumn, adaptability, the character, the district, virginity, maturity, fearless, free and cruel.